Deadlines and disruption [ my turbulent path from print to digital - Shepard, Stephen B. (McGraw-Hill, 2013)
Is this the beginning of an irreversible slide into third-rate journalism? Or the start of a better world of interactive, multimedia journalism? This title tackles all the tough questions facing journalists, the news industry, and, indeed, anyone who understands the importance of a well-informed public in a healthy democracy